Nilai-Nilai Pendidikan Islam Dalam Tradisi Tahlilan Di Desa Batu Melenggang Kecamatan Hinai - Satria Wiguna; Ahmad Fuadi (Thawalib: Jurnal Kependidikan Islam, 2022)
In general, the tradition of praying for the dead is an activity carried out by reading the phrase "Laa Ilaaha Illa Allah". The purpose of the study was to determine the application of Islamic education values in the tradition of praying for the dead in Batu Melenggang Village, Hinai District, Langkat Regency. The research method uses qualitative research methods with data collection techniques, namely observation, interviews and documentation. The object of this research is the villagers of Batu Melenggang, Hinai District. The first data analysis technique examines in depth the problem, then interprets the data and adapts it to the theory, and finally concludes all of the research results. The results of the research on the values of Islamic education in the tradition of praying for the dead are the value of alms, the value of mutual assistance, the value of solidarity, the value of harmony, the value of silaturrahim as ukhuwah Islamiyah, the value of the virtue of dhikrulmaut (remembering death), the value of the virtue of dhikrullah (remembering Allah swt).), elements of da'wah, and health values. The implementation of the tradition of praying for the dead in the Batu Melenggang Village community, Hinai District, is often held when the sun has set or after Maghrib. The event to pray for the dead only starts when many invitees have come and are considered sufficient and usually the tradition is carried out with the practices of reading the Qur'an and dhikr.